If the roots of the equation (b-c)x*2+(c-a)x+(a-b)=0are equal then.Prove that 2b=a+c
Attachments:
![](https://hi-static.z-dn.net/files/d9f/db992df1c3c66f768bf9cdf743d4e969.jpg)
Answers
Answered by
0
Answer:
jduuenhxisn
Step-by-step explanation:
ndifnfocnkeuzmlelnacwi fx
Answered by
3
Given:
To Prove:
How to Solve?
We can solve by using Discriminant.
What is discriminate?
The discriminant is the part of the quadratic equation in which contains (coefficient of x)² - 4(coefficient of x²)(constant). The discriminant tells us whether there are two solutions, one solution, or no solutions.
When the quadratic equation has equal roots then the discriminant is equal to zero.
Solution:
Comparing the (b - c)x² +(c - a)x + (a - b) = 0 equation from basic equation Ax² + Bx + C = 0, I get....
A = (b - c), B = (c - a) , C = (a - b)
Since Roots are equal So discriminate is
B² - 4AC = 0
See in the attachment
Attachments:
![](https://hi-static.z-dn.net/files/d14/d541b9304d96242d603c587b702a0e82.jpg)
Similar questions